2013
DOI: 10.1002/pola.26654
|View full text |Cite
|
Sign up to set email alerts
|

One‐step synthesis of block‐graft copolymers via simultaneous reversible‐addition fragmentation chain transfer and ring‐opening polymerization using a novel macroinitiator

Abstract: One‐step synthesis of block‐graft copolymers by reversible addition‐fragmentation chain transfer (RAFT) and ring‐opening polymerization (ROP) by using a novel initiator was reported. Block‐graft copolymers were synthesized in one‐step by simultaneous RAFT polymerization of n‐butylmethacrylate (nBMA) and ROP of ε‐caprolacton (CL) in the presence of a novel macroinitiator (RAFT‐ROP agent). For this purpose, first epichlorohydrin (EPCH) was polymerized by using H2SO4 via cationic ring‐opening mechanism. And then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 76 publications
1
14
0
3
Order By: Relevance
“…Hence, it may be expected that they have shorter poly(2-vinylpyridine) segments, which is confirmed by a decrease in the molecular weights of the graft copolymers, as shown in Table 1. The same situation was also observed in our previous articles (58)(59)(60). Increasing the amount of monomers also generally causes an increase in both the yield and the molecular weights of the copolymers as expected.…”
Section: Synthesis Of Poly(vinyl Chloride-graft-2-vinylpyridine) Grafsupporting
confidence: 78%
See 2 more Smart Citations
“…Hence, it may be expected that they have shorter poly(2-vinylpyridine) segments, which is confirmed by a decrease in the molecular weights of the graft copolymers, as shown in Table 1. The same situation was also observed in our previous articles (58)(59)(60). Increasing the amount of monomers also generally causes an increase in both the yield and the molecular weights of the copolymers as expected.…”
Section: Synthesis Of Poly(vinyl Chloride-graft-2-vinylpyridine) Grafsupporting
confidence: 78%
“…At higher amounts of monomer, a deviation from normal behavior was observed. This situation could be attributed to the increase in viscosity of the polymerization medium as shown in our previous articles (24,60). Dependence of 2-vinylpyridine concentration on M n for the copolymerization is shown in Figure 3.…”
Section: Code Raft Macroinitiator 2-vinylpyridine Time (Min) Yield (Gmentioning
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the research on poly (N‐isopropylacrylamide) (PNIPAM) block copolymer is more systematic and in‐depth . However, due to its poor biocompatibility and low LCST, it has seriously affected its future application prospects. Recent studies have shown that the biocompatibility of poly ( N N ‐diethylacrylamide) (PDEA) is far superior to that of PNIPAM, and its LCST is also higher than that of PNIPAM.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, ROP have been combined with other polymerization processes in order to obtain polymers with specific properties. For example, RAFT and ROP have been employed in a one‐step route to synthesize well‐defined copolymers . The reaction is mediated by a bifunctional compound (i.e.…”
Section: Introductionmentioning
confidence: 99%